Mapping of Seafloor and Delineating Coral Reefs of Southern Iraq/Northwest Arabian Gulf by Side Scan Sonar Technique - Al-Rawi, F.T.; Al-Mosawi, W.M.; Al-Tememi, M.K. (Mesopotamian Journal of Marine Sciences, 2022)
High-resolution Side Scan Sonar data, under-water observation (video and photograph) and bottom samples (rocks and sediments) were integrated to map the seafloor of the Palinurus shoal which is one of the submerged shoal site in the Iraqi territorial marine, Northwest region of the Arabian Gulf. The Side Scan Sonar field survey was carried out along with eight parallel profile extending in SE-NW direction, at a length of 2.8 km for each line. Four backscatter patterns were mapped within the study area. The pattern reflects various seafloor lithology. The average depth of sea bottom was determined at 7 - 10 m. Coral Reefs were mainly found at two parts of the shoal site in the formed assemblages and sporadic in central and northern parts of the site respectively. These coral take different shapes, sizes and colors. Also, they are live in some places and dead in others.